Pembentukan Pos Upaya Kesehatan Kerja pada Industri Kecil Pembuat Alat Rumah Tangga di Kelurahan Bugangan Kota Semarang - Denny, Hanifa Maher; Jayanti, Siswi; Setyaningsih, Yuliani; Umamah, A’izzatul; Pigoramdhani, Ardhy P. (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: Bugangan Village is one of the central location of making metal household appliances in Semarang. Workers were vulnerable to exposure by hazard risk factors in the work environment, thus at risk of occupational accidents and occupational diseases. In these locations require the Pos Upaya Kesehatan Kerja (UKK). The purpose of this activity was to established a safet and health post for a group of household appliance makers so that workers in the location can work safely, health and productive. Method: This research was used qualitative approach. The technical activities that was done collaborated between Semarang Health Office and Bugangan Public Health Center. The team also held discussions to the chairman and vice chairperson of the Bina Warga community so that the activities could run smoothly. Results: The result obtained from this activity was the establishment of UKK Post Metal Products located in one of the workers house. For the sustainability of Pos UKK, the attendant puskesmas officers have been willing to nurture the established UKK Post, and officers from Semarang health office were willing to build and supervise the community heath center (puskesmas) staff. Conclusion: The conclusion of this activity was to the established the UKK Post successfully implemented by involving entrepreneurs, domestic appliance industry workers in Bugangan, Bugangan Puskesmas, and Semarang City Health Office.